2014
DOI: 10.1371/journal.pone.0094752
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Preparation of Large Quantities of Complex Single-Stranded Oligonucleotide Libraries

Abstract: Custom-defined oligonucleotide collections have a broad range of applications in fields of synthetic biology, targeted sequencing, and cytogenetics. Also, they are used to encode information for technologies like RNA interference, protein engineering and DNA-encoded libraries. High-throughput parallel DNA synthesis technologies developed for the manufacture of DNA microarrays can produce libraries of large numbers of different oligonucleotides, but in very limited amounts. Here, we compare three approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
(38 reference statements)
0
54
0
2
Order By: Relevance
“…Denaturing poly-acrylamide gel electrophoresis and absorption spectroscopy were used to confirm the quality of the probes and revealed that this probe synthesis protocol converts 90–100% of the reverse-transcription primer into full length probe and of the probe that is constructed, 70–80% is recovered during the purification step. This protocol is similar to another recently published protocol (23) but provides a substantially larger yield. …”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Denaturing poly-acrylamide gel electrophoresis and absorption spectroscopy were used to confirm the quality of the probes and revealed that this probe synthesis protocol converts 90–100% of the reverse-transcription primer into full length probe and of the probe that is constructed, 70–80% is recovered during the purification step. This protocol is similar to another recently published protocol (23) but provides a substantially larger yield. …”
Section: Methodsmentioning
confidence: 79%
“…To generate the massive number of encoding probes required, we amplified them from array-derived oligonucleotide pools containing tens of thousands of custom sequences using a modified form of the oligopaint protocol comprising in vitro transcription followed by reverse transcription (Fig. S3; Materials and Methods, “Probe Synthesis” section) (22, 23). This two-step labeling approach significantly diminished the total hybridization time for an experiment: we found that efficient hybridization to the readout sequences took only 15 minutes whereas efficient direct hybridization to cellular RNA required more than 10 hours.…”
Section: Combinatorial Labeling With Error-robust Encoding Schemesmentioning
confidence: 99%
“…Each synthesized library contained 400 ng DNA. The libraries were first amplified using an emulsion PCR protocol (Murgha et al 2014). Briefly, the PCR mixture (aqueous phase,100 ml) consisted of 0.2 ng DNA from the library, 0.5 mM each of F (T7 RNA polymerase promoter plus 6 additional nucleotides) and R (CGTGGTCGCGTCTCA) primers ( Figure 1B), 0.2 mM dNTPs, 0.5 mg/ml bovine serum albumin, 4 units of Phusion High-Fidelity polymerase (New England Biolabs, catalog no.…”
Section: Probe Preparation From Synthesized Oligo Librariesmentioning
confidence: 99%
“…Finally, 288 (6.92%) of the 4161 RNA molecules were not detected across the 9 arrays for the 3 detection experiments, namely: RNA library composition, unlabeled RNA library by reporter DNA library, and post-labeling of unlabeled RNA to confirm reporter DNA calls. The missing oligonucleotides in each of the respective custom libraries may be attributed to any of the following: synthesis failure, drop-out during in vitro transcription or reverse transcription, hybridization failure (probe synthesis failure, secondary structure, steric hindrance), or a concentration of individual oligonucleotides that is below the detection threshold (17). …”
Section: Resultsmentioning
confidence: 99%
“…For example, the process is modified to generate multiple fluorescent sub-libraries for FISH from a single de novo synthesized library. Finally, the process can be scaled up to produce several hundred micrograms of labeled probe libraries (17). …”
mentioning
confidence: 99%